Capnography Improves Detection of Apnea During Procedural Sedation for Percutaneous Transhepatic Cholangiodrainage - Christoph Schlag; Alexandra Wörner; Stefan Wagenpfeil; Eberhard F Kochs; Roland M Schmid; Stefan von Delius (Canadian Journal of Gastroenterology)
BACKGROUND: Capnography provides noninvasive monitoring of ventilation and can enable early recognition of altered respiration patterns and apnea.